Recursos e capacidades para literacia em tecnologia de informação: uma estratégia orientada a stakeholders - Lauand, Mauricelio (2020)
One of the elements of change that has most provided transformations in the business environment and society as a whole, is digital transformation. For institutions to folow technological developments, it is necessary professionals well educated to drive the competitiveness of companies and countries (BOWMAN; AMBROSINI, 2003). From this, the general objective of this study is to identify the resources and capabilities that generate literacy in information technology, of a Higher Education Institution (HEI) with a stakeholder-oriented strategy. Literacy in information technology is the key to empowerment today and it is through education that demand has been supplied by skilled IT workers in a constant way. Equal challenge is how to build a higher education system in information technology, as traditional models of higher education institutions may not meet the requirements for the latent needs of societies. For this scope of IT training it is essential that HEI have strategic vision and stakeholder-oriented business management, in order to generate value to shareholders, market, students and society fundamentally. The integration between educational and business environments enhances the fulfillment of both parties' needs by improving digital transformation. It is in this context that this research project develops, seeking to answer the following research question: What resources and capabilities provide literacy in information technology in a stakeholder-oriented HEI?